Swift, NuStar, and XMM–Newton observations of the NLS1 galaxy RX J2317.8–4422 in an extreme X-ray low flux state. Issue 1 (20th March 2019) - Grupe, Dirk; Komossa, S; Gallo, Luigi; Schartel, Norbert; Parker, Michael; Santos-Lleo, Maria; Fabian, Andrew C; Harrison, Fiona; Miniutti, Giovanni
Abstract: We report the discovery of RX J2317.8–4422 in an extremely low X-ray flux state by the Neil Gehrels Swift observatory in 2014 April/May. In total, the low-energy X-ray emission dropped by a factor of 100. We have carried out multiwavelength follow-up observations of this narrow-line Seyfert 1 galaxy. Here we present observations with Swift, XMM–Newton, and NuSTAR in 2014 October and November and further monitoring observations by Swift from 2015 to 2018. Compared with the beginning of the Swift observations in 2005, in the November 2014 XMM–Newton and NuSTAR observations RX J2317–4422.8 dropped by a factor of about 80 in the 0.3–10 keV band. While the high-state Swift observations can be interpreted by a partial covering absorption model with a moderate absorption column density of NH = 5.4 × 10 22 cm −2 or blurred reflection, due to the dominating background at energies above 2 keV the low-state XMM–Newton data cannot distinguish between different multicomponent models and were adequately fitted with a single power-law model. We discuss various scenarios like a long-term change of the accretion rate or absorption as the cause for the strong variability seen in RX J2317.8–4422.